“Gamblification” of sport and new generations - Moriconi, M.; Cima, C. (Play the Game Conference 2025, 2025)
In recent years there has been a growing influence of the gambling industry into the world of sport and sporting culture, which the literature has described as the "gamblification of sport". Bookmakers dominate sponsorship in the sports sector, states have increased their dependence on tax revenues from gambling and advertising for sports betting takes up more and more airtime on television and radio. Consequently, sports betting is becoming increasingly normalised in society. Although the liberalisation of gambling is an inevitability (given the ease of access to illegal markets), the absence of regulations establishing restrictions on sponsorship in the sports ecosystem and on sports betting advertising in several countries, such as Portugal, has been exposed risk groups to addiction. At this level, the literature has identified young people (18-35) and athletes as two particularly vulnerable social groups. Social scientists have made advances in knowledge by measuring the prevalence levels of (pathological) gambling in these (and other) social groups, and studying the social problems related to pathological gambling (debts, mental health, social isolation, suicide). However, there is a lack of data clarifying the percentage of young Portuguese at risk of pathological gambling; there is little knowledge about the prevalence of gambling (recreational or problematic) in amateur sports at international level; and the relationship between gambling (pathological or not) and match-fixing remains undertheorized. Furthermore, the consequences of gambling for society are not limited to the harmful effects of pathological gambling. For example, the concept of “gamblification” was coined to explain the new habits of consuming sporting events not for the sport itself, but for sports betting, but this theorical proposition has yet to be empirically test. The aim of this research and its innovative nature is, precisely, to evaluate in what extent the "gamblification of sport” have been changed the consumption of and the interest in sports events in young people and athletes in Portugal, and what kind of risks this represent for society and integrity of sports. The research question is divided into four objectives that expand the literature: 1) to examine the prevalence levels of gambling in young people (18-35) and amateur athletes in Portugal; 2) to understand in what extent betting is normalised in Portuguese society and the role that gambling plays in the consumption of sport events in young people and amateur and semi-professional athletes; 3) to explore the new threats for sports integrity and social health, not necessarily related to pathological gambling; 4) to map international good practices and suggest public policies that mitigate the harmful effects of the "gamblification of sport”.